BINTU SYATIâ DAN PENAFSIRANNYA TERHADAP SURAH AL-âASR DALAM KITAB AT-TAFSIR AL-BAYANI LIL QURâANIL KARIM - Ramadhani, Wali (Jurnal At-Tibyan: Jurnal Ilmu Alquran dan Tafsir, 2018)
This article discusses about the biography of Bintu Syatiâ and her bayani interpretation. Her Interpretation work titled at-Tafsir al-Bayani lil Quranil Karim is the best representation of the methodology of the Quran interpretation with a literary nuance initiated by her own husband, Amin al-Khuli. The author, in this article, also describes the application of Bayani interpretation method in QS al-âAs}r.